MANAGEMENT ACCOUNTING SYSTEM OF PUBLIC OFF-BUDGET FUNDS AS AN INFORMATIONAL BASIS FOR PUBLIC INSURANCE MECHANISMS FORMATION (CASE STUDY OF FEDERAL COMPULSORY MEDICAL INSURANCE FUND) - Anatoly A. Kozlov (Статистика и экономика)
The article justiﬁes the introduced proposals for a management accounting of theFederal Compulsory Medical InsuranceFund formation and the characteristics and principles of management accounting forms for the analysis of the territorialcompulsory medical insurance programs.